Phase II trial of hypofractionated VMAT-based treatment for early stage breast cancer: 2-year toxicity and clinical results. Issue 1 (December 2016) - De Rose, Fiorenza; Fogliata, Antonella; Franceschini, Davide; Navarria, Piera; Villa, Elisa; Iftode, Cristina; D'Agostino, Giuseppe; Cozzi, Luca; Lobefalo, Francesca; Mancosu, Pietro; Tomatis, Stefano; Scorsetti, Marta
Abstract Background To report toxicity and early clinical outcomes of hypofractionated simultaneous integrated boost (SIB) approach with Volumetric Modulated Arc Therapy (VMAT) as adjuvant treatment after breast-conserving surgery. Methods Patients presenting early-stage breast cancer were enrolled in a phase II trial. Eligibility criteria: age > 18 years old, invasive cancer or ductal carcinoma in situ (DCIS), Stage I-II (T < 3 cm and N ≤ 3), breast-conserving surgery without oncoplastic reconstruction. Any systemic therapy was allowed in neoadjuvant or adjuvant setting. All patients underwent VMAT-SIB technique to irradiate the whole breast and the tumor bed. Doses to whole breast and surgical bed were 40.5 Gy and 48 Gy, respectively, delivered in 15 fractions over 3 weeks. Acute and late skin toxicities were recorded. Cosmetic outcome was assessed as excellent/good or fair/poor. Results The present study focused on results of a cohort of 144 patients with a minimum follow-up of 24 months (median 37, range 24–55 months). Median age was 62 years old (range 30–88). All patients had an invasive carcinoma (no patients with DCIS were present in this subset). At one year, the highest reported skin toxicity was G1, in 14 % of the patients; this data dropped to 4 % at the last follow-up, after more than 2 years. Breast pain was recorded in 21.6 % of the patients 6 months after treatment, while it was present in 3.5 % of the patients at the last follow-up, showing a significant improvement with time. Correlation between liponecrosis and boost target volume was found not significant. Breast pain was correlated with breast volume. No pulmonary or cardiological toxicities were recorded. After an early evaluation of clinical outcomes, only one case presented disease relapse, as liver metastases. Conclusions The 3-week VMAT-SIB course as adjuvant treatment after breast-conserving surgery showed to be well tolerated and was associated with optimal local control. Long-term follow-up data are needed to assess late toxicity and clinical outcomes.